KNOWLEDGE, ATTITUDE, AND PRACTICES OF MOTHERS TOWARDS CHILD IMMUNIZATION SCHEDULE COMPLIANCE AT MASAKA REGIONAL REFERRAL HOSPITAL, MASAKA DISTRICT. A CROSS-SECTIONAL STUDY. - Nanyondo , Prosam; Odiwuor, Joash Otieno (Student’s Journal of Health Research Africa, 2023)
Background: The burden of unimmunized children in Uganda is 48% of children under the age of five years who are not immunized at all or partially immunized meaning some of them start immunization but do not complete the immunization schedule. Objectives: The study is intended to explore the knowledge, attitude, and practices of mothers toward child immunization schedule compliance in Masaka Regional Referral Hospital in Masaka District. Methodology: The study was based on a purposive sampling method in which 117 mothers were enrolled in the study; the study employed a structured questionnaire that was administered by the researcher and the research assistants to collect data. Results: The majority of the mothers; were in the 20- 35 age group 50.4%, the Baganda tribe 37.6%, married 45.3% and those who attained secondary education level were 49.6%.53.8% defined immunization as the process of administering vaccines to prevent diseases, 45.3% mentioned about 3 child immunizable diseases, 89.7% were sensitized about the importance of immunization towards their children’s health and 63.2% agreed that their children’s immunization schedule was according to the recommended immunization guidelines. Conclusions: The study findings indicate that the majority of the mothers know child immunization, its importance on their children’s health when a child needs to be vaccinated, the VPDs, and the recommended sites for different vaccines. Recommendations: Based on the findings in the study it is recommended that the government should come up with programs creating awareness concerning the importance of child immunization as well as providing health education to parents about vaccine-preventable diseases.